PENGUATAN LITERASI ANAK DAN EKONOMI KREATIF BERBASIS KELUARGA MELALUI PROGRAM CALISTUNG DI RUMAH LITERASI RANGGI - Cindy Hutabarat; Sardi Pranata; Debora Simbolon; Grace Tarigan; Hegel Barus; Kasihati Bulolo; Lina Gultom; Sheril Fadia; Siska Sitanggang; Zaskia Aisyah (Jurnal Keluarga Sehat Sejahtera, 2025)
This research explores the execution of an integrated literacy and creative economy initiative targeting children at Ranggi Literacy House, combining fundamental academic skills (reading, writing, arithmetic) with hands-on bracelet craft activities. Employing a descriptive qualitative methodology through observation, interview, and documentation methods, this investigation engaged 20 participants between 7 and 12 years old. Findings revealed that vertical multiplication presented significant challenges for the majority of participants, necessitating dedicated guidance and support. The synergistic approach of academic instruction paired with craft production demonstrated notable improvements in children's learning concentration, foundational mathematical abilities, and personal confidence levels. Through creative economy activities, participants gained exposure to elementary production workflows and manual skill-based innovation. This study contributes a community-based integrated literacy–creative economy model for children from low-income families. Beyond skill development and creative stimulation, this initiative offers practical implications for families and communities seeking replicable empowerment frameworks in comparable settings.